Prova Brasil e Prova SAEP: (in)convergências teóricas e metodológicas no campo da linguagem - Záttera, Pricilla (2017)
The quality of Brazilian education has often been on the agenda of discussions and reflections of researchers and educators, whether in what concerns the classroom floor or in the production and socialization of scientific knowledge transformed into teaching content, or in terms of public policies in the educational field. Although they are close dimensions, in this research, we turn towards public policies, making the cut for one of its components, the large-scale evaluations, which are presented as balancers, among other aspects, of advances (or not), in learning from the students. With its advent in the 1990s, large-scale external evaluations have taken center position in educational policies, and are also a parameter for decision-making regarding investments or financial cuts to school. Among the evaluation systems in Brazil, and imposed in schools, two are highlighted: The Brazilian National Basic Education Assessment System, known as SAEB, which develops the Prova Brasil (a population-based assessment of public schools applied to 5th and 9th grade students) and the Paraná Basic Education Assessment System (SAEP), which develops the Saep assessment (applied to 6th and 1st year students, 9th and 3rd year students). Both systems assessment focuses only on the Portuguese Language and Mathematics subjects. Considering the importance that has been assigned to SAEB / PB and SAEP / PS, leading school systems to adopt one-off measures (such as preparatory courses, for example) to obtain quantitative results that attest to the quality of teaching and learning, we raised the following problem with the Portuguese language test: because they are evaluation systems aimed at the same students, who attend the same schools, are there any interrelations between their objectives, their methodologies and their conceptions of language and reading? This enquiry was questioned through a qualitative, interpretative research of socio-historical approach, of documentary analysis, situated in the Applied Linguistics studies field, aiming to observe if there are interrelations between these systems regarding to the mentioned aspects, and about how this dialogue happens. To fulfill this objective, we first describe and analyze the configuration of these systems through the study of official documents, and then proceed to the comparison of approximations and / or distances between them. As results, we find that these evaluations are convergent, especially with regard to methodology and conceptions of language and reading. Regarding the inconsistencies found, they occur in the formulation of the objectives of the evaluations, more specifically in the availability of the results of these evaluations.